Application of resistance training in women with fibromyalgia - Raúl Ferrández Belén; Iván Chulvi Medrano; Laura Masiá Tortosa (Federación Extremeña de Balonmano; University of Extremadura, 2020)
Introduction: Fibromyalgia (FM) is a rheumatic disease associated with fatigue and chronic pain with a high prevalence in women, FM impair the quality of life. It has been recommended physical exercise as a non-pharmacological therapy. Therefore, the objective was to assess and analyze the effects of a resistance training program with elastic bands in women diagnosed with FM Method: 6 women diagnosed with FM, with a mean age of 56 (5.73) years, completed an elastic bands resistance training program with a duration of 5 weeks at a rate of 2 days per week. Before and after the intervention, were evaluated: i) Quality of life (SF-36); ii) The impact of the disease (FIQ); iii) The physical condition (Senior Fitness Test); iv) Sleep quality (PSQI). Results: It was registered, significant improvements were obtained on the impact of the disease (18.5%), quality of life (30%) and strength in upper (23%) and lower (28%) body. Conclusion: A circuit of resistance training program with elastic bands and bodyweight exercise obtained improvements in lower and upper body muscle strength and quality of life without worsening the symptoms of the disease.